Dissensus Efforts in Kawali dan Pistol by Alfian Dippahatang - Dwi Rezki Hardianto Putra Rustan (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
This study uses the short story Kawali and Pistol (KDP) by Alfian Dippahatang as a material object, and Jacques Ranciere's aesthetic politics concept as a formal object. This study aims to (1) reveal the form of sensibility distribution based on the environment of the two main characters in KDP, (2) examine the dissensus efforts of the main characters as subjects in KDP. The method used is descriptive qualitative by analyzing the data using the historical hermeneutic method. The results of the research (1) KDP has illustrated the arche of the Bugis-Makassar society. KDP also based on imitations produces of localities in Bugis-Makassar. (2) KDP opens a space for dissensus within the police for allows the process of subjectivication demos in the Bugis-Makassar society. However, with the presence of the disensus space, Ramlah and Rungka failed to act politically. Their equality is just a mere assumption, not in the realm politics.